1989
DOI: 10.1007/bf00261164
|View full text |Cite
|
Sign up to set email alerts
|

The gene family encoding the Arabidopsis thaliana translation elongation factor EF-1α: Molecular cloning, characterization and expression

Abstract: The gene family encoding the Arabidopsis thaliana translation elongation factor (EF-1 alpha) was analysed. This family contains four genes (A1-A4) organized in a similar manner in different varieties of Arabidopsis. Based upon both their physical separation and a comparison of their sequences, it is suggested that the A4 gene and the A1, A2, and A3 genes constitute two distinct subfamilies within the genome. By introducing chimaeric gene constructs into Arabidopsis cells, we showed that the A1 gene promoter me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 37 publications
2
112
0
2
Order By: Relevance
“…In tomato (Pokalsky et al, 1989), tobacco (Ursin et al, 1991;Marty et al, 1993), and possibly Arabidopsis (Curie et al, 1993), elevated levels of EF-lu gene expression were indicated in developing tissues. Auxin (Ursin et al, 1991), low temperature (Dunn et al, 1993), and light (Aguilar et al, 1991) appear to modulate expression of some EF-lu genes, and multigene families are present in severa1 plants (Axelos et al, 1989;Pokalsky et al, 1989;Aguilar et al, 1991;Dunn et al, 1993). A gene family has been found in carrot cells as well (Kawahara et al, 1992), and Figure 46 presents data consistent with this finding.…”
Section: Gene Expression During Developmentsupporting
confidence: 61%
“…In tomato (Pokalsky et al, 1989), tobacco (Ursin et al, 1991;Marty et al, 1993), and possibly Arabidopsis (Curie et al, 1993), elevated levels of EF-lu gene expression were indicated in developing tissues. Auxin (Ursin et al, 1991), low temperature (Dunn et al, 1993), and light (Aguilar et al, 1991) appear to modulate expression of some EF-lu genes, and multigene families are present in severa1 plants (Axelos et al, 1989;Pokalsky et al, 1989;Aguilar et al, 1991;Dunn et al, 1993). A gene family has been found in carrot cells as well (Kawahara et al, 1992), and Figure 46 presents data consistent with this finding.…”
Section: Gene Expression During Developmentsupporting
confidence: 61%
“…Protoplasts were prepared from an Arabidopsis thaliana (Columbia ecotype) cell suspension culture (lhe T87) according to Axelos et al (1989). Cells were grown on MS medium supplemented with 1 pM naphthaleneacetic acid (Axelos et al, 1989) and collected at the midexponential growth phase.…”
Section: Hmgp-gus Gene Fusionsmentioning
confidence: 99%
“…Cells were grown on MS medium supplemented with 1 pM naphthaleneacetic acid (Axelos et al, 1989) and collected at the midexponential growth phase. Transfections were performed according to the Ca(NO&polyethylene glycol technique as described by Prols et al (1988) using 40 pg of cesium chloride-purified plasmid DNA and 107 protoplasts.…”
Section: Hmgp-gus Gene Fusionsmentioning
confidence: 99%
“…Because of the presente of a second Ncol site within the MtENOD12 promoter (Figure 2), it was necessary to carry out a partial digestion of pUC19-prMtl2 after linearization with EcoRl to recover the full-length 23-kb EcoRI-Ncol fragment. This promoter fragment was then cloned between the EcoRl and Ncol polylinker sites of pCCOGUS (Axelos et al, 1989) so that subsequent digestion with EcoRl and Pstl would yield a DNA fragment containing the MtENOD12 promoter fused to the gusA coding sequence with a 3' flanking polyadenylation signal (cauliflower mosaic virus 35s). After adding an Sstl site to the 3'terminus, the resultant fragment was cloned between the unique EcoRl and Sstl sites of the binary vector pLPl00 to give pLP100-prMt12.…”
Section: Promoter-gusa Fuslonmentioning
confidence: 99%